Peran Guru PAI dalam Peningkatan Resiliensi Akademik Peserta Didik di MTs Al-Yusra Kota Gorontalo - Ririn Anggreani Mantuges; Bayu Saputra Dullah; Faizal Fatah SN Tuli (STIT Al-Ittihadiyah Labuhanbatu Utara, 2026)
The learning process often presents multidimensional pressures that demand psychological resilience of students. This study aims to examine the strategic role of Islamic Religious Education Teachers (PAI) in increasing the academic resilience of students at MTs Al-Yusra, Gorontalo City. This research uses a qualitative approach with a descriptive design. Data were collected through participatory observation, semi-structured interviews with PAI teachers, students, and homeroom teachers, and documentation studies. Data analysis is carried out inducively through reduction, presentation, and drawing conclusions. (Results) The results of the study show that students' academic resilience is in a dynamic phase; characterized by strength in aspects of social support and spiritual connection, but has vulnerability to adaptive coping strategies, positive thinking, and emotion regulation. PAI teachers act as catalysts through four main functions: facilitator of critical thinking, provider of contextual material, meaning-based motivator, and spiritual role model (uswatun hasanah). The effectiveness of this role is hampered by student heterogeneity, inconsistencies in family support, and administrative burden. The integration of Islamic values such as sabr and tawakkal has been proven to function as an effective cognitive reframing mechanism. This study concludes that optimizing resilience requires pedagogical-spiritual synergy and school-family collaboration. The main contribution of this study is to offer a psychopedagogical intervention model based on Islamic spirituality that can be adopted by Islamic educational institutions to shape the mental resilience of learners in the contemporary era.